Expression of CXCR3 on specific T cells is essential for homing to the prostate gland in an experimental model of chronic prostatitis/chronic pelvic pain syndrome - Breser, Maria Laura (2013)
Experimental autoimmune prostatitis (EAP) is considered a valid model for the human disease chronic prostatitis/chronic pelvic pain syndrome. In this report, we analyzed phenotypic characteristics of T cells that gain access to the prostate and induce leukocyte recruitment in mice with different susceptibility to EAP. After EAP induction, NOD mice developed a specific cellular response characterized by a mixed Th1/Th17 pattern with specific T cells mainly expressing CXCR3 that infiltrated and damaged the prostate. In contrast, BALB/c mice, as well as NOD-IFN-g2/2, exhibited only Th17 cells mainly expressing CCR6 that were not capable of infiltrating the prostate gland. Adoptive transfer experiments of T cells from NOD or NOD–IFN-g2/2 mice to NOD-SCID recipients showed that only T cells from NOD mice successfully infiltrated the prostate. However, after “in vitro” or “in vivo” treatment with rIFN-g, T cells from NOD–IFN-g2/2 mice became capable of homing to the prostate and induced leukocyte recruitment. Chemokine levels in prostate tissue from NOD mice showed increased expression levels of CXCR3 ligands. Additional experiments using adoptive transfer of sorted CXCR3+ CD3+ T cells or administrating a CXCR3 antagonist treatment confirmed these previous results. Altogether, our results demonstrate that the expression of CXCR3 on effector T cells is essential for their homing to the prostate gland in EAP. CXCR3 emerges as a potential therapeutic target to control chronic prostatitis/ chronic pelvic pain syndrome.